A rare but morbid neurosurgical target: petrous aneurysms and their endovascular management in the stent/flow diverter era. (26th September 2016) - Gross, Bradley A; Moon, Karam; Ducruet, Andrew F; Albuquerque, Felipe C
Abstract : Background/objective: The rarity of petrous internal carotid artery (ICA) aneurysms has largely precluded analyses of their presentation and management in case series format. Methods: We performed a retrospective analysis of our endovascular database of patients treated from January 2001 to May 2016 to identify patients with petrous ICA aneurysms. We evaluated the treatment approach and results for patients managed in the era of dedicated intracranial stents and flow diverters, noting clinical and angiographic results. Results: Our database search identified 10 patients with petrous ICA aneurysms. Six aneurysms were managed in the era of dedicated intracranial stents and flow diverters. Two patients presented with cranial nerve palsies, two with incidental but enlarging aneurysms that had completely eroded through the petrous bone, one with transient ischemic attacks, and one with pulsatile tinnitus. Five aneurysms were large and one was small but symptomatic. In three cases the aneurysm was treated by flow diversion with adjunctive coiling; two patients with at least 4-month follow-up had complete occlusion of their aneurysm and significant improvement of mass effect symptoms. In one case the aneurysm was treated with balloon-assisted coiling with resultant near-complete occlusion. In two cases, prior to the introduction of flow diverters, the aneurysm was treated via stent-assisted coiling with resultant near-complete obliteration; one patient had resolution of pretreatment pulsatile tinnitus. There were no intraprocedural or postprocedural complications; no patients underwent retreatment. Conclusions: Endovascular treatment of large or symptomatic petrous ICA aneurysms, in the era of flow diversion, is associated with excellent angiographic and clinical outcomes.